Eyewitness Memory for Person Identification: Predicting Mugbook Recognition Accuracy According to Person Description Abilities and Subjective Confidence of Witnesses - Handler, Alexander; Frühholz, Sascha (Frontiers in Psychology, 2021)
Mug book searches are conducted, when a suspect is not known, to look if a previously convicted person might be recognized as a potential culprit. The goal of the studies reported here was to analyse if prior statements and information about the suspect can aid in the evaluation if such a mug book search is subsequently advised or not. In the first part of this study memory accuracy for person descriptors was tested to analyse which attributes could be chosen to down-scale the mug book prior to testing. Results showed that age was the most accurate descriptor followed by ethnicity and height. At the same time self-assessed bad subjective accuracy of the culprit description by the witness seemed to be divergent to the objective actual performance accuracy. In the second independent part of the study, a mug-book search was conducted after viewing a video of a staged crime and giving a description of the culprit. Results showed that accuracy in mug-books correlated positively with total person descriptors mentioned as well as with external facial features. Meanwhile predictive confidence (i.e. subjective rating of own performance in the subsequent mug-book search) did not show any relation to accuracy in the actual mug-book search. These results highlight the notion that mug-books should not be conducted according to the subjective estimation of the witness’ performance, but more according to the actual statements and information that the witness can give about the culprit.